Pengembangan Sistem Informasi Akademik Berbasis Web pada SMK Negeri 3 Bone - Sapitri, Pira; Kasim, Syarifuddin; Jaya, Hendra (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2023)
This study aims to determine the results of the development of a web-based Academic Information System at SMK Negeri 3 Bone and the results of testing based on ISO 25010 quality standards. This research uses prototype development model. Data collection techniques using interviews, questionnaires, and documentation. System testing uses the ISO 25010 quality standard which focuses on testing functional suitability, reliability, performance efficiency, usability, portability, security, maintainability, and compatibility. As for the results of testing the system using the ISO 25010 quality standard, namely in the functional suitability test with good criteria, in the reliability test, it was stated that the system met the reliability aspect, in the performance efficiency test the results obtained for the GTMetrix class obtained B score with a performance of 84% structure of 94% and a load time of 2.2 seconds, in the usability test the percentage results are 90.98% in the very feasible category, in the portability test the results can run well on different devices and browsers, testing on the security aspect shows the system's resistance to malware and blacklisting websites has a medium risk so that this information system is safe to access. The website-based academic information system has fulfilled the maintainability aspect, and in testing the compatibility aspect it is stated that the academic information system has fulfilled the compatibility aspect.